The Radical Polymerization of Propargyl Acetate - Moriya, Masafumi; Kimura, Masanobu; Yamashita, Tadataka (Kobunshi Kagaku, 1971)
The bulk polymerization and copolymerization of propargyl acetate (PAc) have been studied by using azobisisobutyronitrile and benzoylperoxide (BPO) as initiators. The resulting homopolymers were yellow, oily and soluble in almost organic solvents, and the molecular weights of the polymers were very low. The rate of polymerization (Rp) at 80°C was expressed by the following equation: Rpαk [BPO] 0.8. The apparent activation energy in the overall polymerization was obtained to be 4.60kcal/mol. In the copolymerization of PAc-St and PAc-AN systems, it has been found that the rate of polymerization of these systems decreases remarkably, as the mole fractions of PAc in the comonomer increase. The monomer reactivity ratios determined were as follows at 60°C. PAc-St (M1): r1=53.0, r2=0.00, PAc-AN (M1): r1=6.15, r2=0.05.